A Note on Wave Equation and Convolutions. (9th March 2008) - Kılıçman Kılıçman, Adem Adem; Eltayeb Eltayeb, Hassan Hassan
Abstract : We study the first-order nonhomogenous wave equation. We extend the convolution theorem into a general case with a double convolution as the nonhomogenous term. The uniqueness and continuity of the solution are proved and we provide some examples in order to validate our results.